Design of a Verilog HDL-Based Advanced Intelligent Automatic Railway Gate Control System - Meher Abbas; Pothuraju Poojitha; Pithani Harika; Perabattula Sri Rama Durga Satya Swamy; Narni Venkata Durga Anjan Kumar; Harika Pangam; M S S Sudheer Naidu (International Journal of Electronics Automation, 2026)
Human mistake, sluggish reaction times, and manual gate operation are common causes of railway level crossing accidents. This project suggests an Intelligent Automatic Railway Gate Controller made with Verilog HDL and simulated in Xilinx Vivado to lessen these mishaps. With the goal of improving safety at unmanned railway crossings, the system is intended to offer a dependable and entirely automated solution. Without human interaction, the railway gate is automatically controlled by the system. A siren alerts those in the vicinity of the crossing that the gate will shortly close when a train gets close to the detecting point. The gate automatically closes following the warning. Additionally, the design is optimized for low power consumption and high-speed performance, making it highly suitable for real-time FPGA-based applications. The gate opens automatically when the train passes the crossing and arrives at the second detecting point. By lowering human error, offering quicker reaction times, and guaranteeing dependable gate operation, this technology enhances railway safety. The design is optimized for low power consumption and high-speed performance, making it highly suitable for real- time FPGA-based applications. With its excellent dependability, low power consumption, and effective traffic control at railway crossings, the design is appropriate for FPGA implementation.
Keywords: Automatic Railway Gate Controller; FPGA; Intelligent Transportation System; Level Crossing Automation; Railway Safety; Verilog HDL; Xilinx Vivado